2019
DOI: 10.1177/0032885519860852
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-Methods Process Evaluation of the Art of Yoga Project for Girls in Custody

Abstract: Many adolescent girls in custody have extensive histories of profound childhood trauma and abuse. They typically come from marginalized communities marked with gang violence. The Art of Yoga Project provides a gender-specific, trauma-informed, and culturally sensitive approach to cater to this understudied and underserved population. The Yoga and Creative Arts Curriculum combines yoga, mindfulness, meditation, and art for girls in custody in several Californian counties. The findings are from a mixed methods e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Most studies described or evaluated a tertiary intervention ( n = 10), and few studies examined primary ( n = 2), or secondary ( n = 2) interventions (see Table 2 ). Half of the studies examined young women who were incarcerated, including in youth detention ( n = 6) ( Arnold et al, 2002 ; Emerson & Shelton, 2001 ; Middleton et al, 2019 ; Palidofsky & Stolbach, 2012 ; Roe-Sepowitz et al, 2009 ; Shekar et al, 2020 ) and in an adult county jail ( n = 1) ( Pomeroy et al, 2001 ). Two studies examined community-based samples, including young women who were released from detention ( n = 1) ( Harris & Malone, 2014 ) or on probation ( n = 1) ( Davidson et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies described or evaluated a tertiary intervention ( n = 10), and few studies examined primary ( n = 2), or secondary ( n = 2) interventions (see Table 2 ). Half of the studies examined young women who were incarcerated, including in youth detention ( n = 6) ( Arnold et al, 2002 ; Emerson & Shelton, 2001 ; Middleton et al, 2019 ; Palidofsky & Stolbach, 2012 ; Roe-Sepowitz et al, 2009 ; Shekar et al, 2020 ) and in an adult county jail ( n = 1) ( Pomeroy et al, 2001 ). Two studies examined community-based samples, including young women who were released from detention ( n = 1) ( Harris & Malone, 2014 ) or on probation ( n = 1) ( Davidson et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…While the individual focuses on their emotions, they are instructed by a facilitator to remain focused on their breathing and to be open to drifting thoughts and emotions during the exercise without judgment (Leonard et al, 2013). In addition to breathing exercises, other examples of mindfulness training include yoga and meditation (Ferszt et al, 2009; Middleton et al, 2019). Overall, studies examining the effect of diverse mindfulness programs have revealed positive program effects (e.g., Dewey et al, 2019; Leonard et al, 2013; Middleton et al, 2019; Rousseau, et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Keehan (2015, p. 215), for example, writes, ‘a repeated theme in the discourse on theater practice in prisons over the last 20 years can be summarized as follows: theater and drama projects have a positive effect on those incarcerated and may contribute toward rehabilitation.’ Cheliotis (2012, p. 32) similarly notes that artists working in prisons tend to draw on a rehabilitative approach to justify the value of the programs, suggesting that ‘offender rehabilitation through the arts has been increasingly tied to the tangible and highly appealing goal of recidivism reduction’ (see also Johnson et al, 2011). We even note that scholars in evaluating prison arts- and wellness-based programs, in this case a yoga and creative arts project, express regret at their inability to tie their results to recidivism rates, stating: ‘Although we would very much like to speak to the impact of this curriculum on recidivism, we simply did not have the resources or the access to conduct a community follow-up’ (Middleton et al, 2019, p. 44S).…”
Section: Rejecting the Institutional Logics Of Arts Programmingmentioning
confidence: 99%